2016
DOI: 10.1371/journal.pone.0157487
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Stimulates Dopamine Tubular Transport by Organic Cation Transporters: A Novel Mechanism to Enhance Renal Sodium Excretion

Abstract: The aim of this study was to demonstrate the effects of atrial natriuretic peptide (ANP) on organic cation transporters (OCTs) expression and activity, and its consequences on dopamine urinary levels, Na+, K+-ATPase activity and renal function. Male Sprague Dawley rats were infused with isotonic saline solution during 120 minutes and randomized in nine different groups: control, pargyline plus tolcapone (P+T), ANP, dopamine (DA), D-22, DA+D-22, ANP+D-22, ANP+DA and ANP+DA+D-22. Renal functional parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In contrast to Ang II, atrial natriuretic peptide (ANP) is a major inhibitory hormone of proximal nephron transport [ 43 , 44 ]. Elevated plasma ANP stimulates urinary Na + excretion during volume expansion [ 45 ], such as likely occurs during fructose-induced salt sensitive hypertension, and it enhances urinary Na + excretion in part through actions on the proximal tubule [ 46 ]. Activation of protein kinase C by Ang II blunts the effects of ANP [ 47 , 48 ] and acute fructose treatment enhances the effects of Ang II via protein kinase C when rats are fed a low-salt diet [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Ang II, atrial natriuretic peptide (ANP) is a major inhibitory hormone of proximal nephron transport [ 43 , 44 ]. Elevated plasma ANP stimulates urinary Na + excretion during volume expansion [ 45 ], such as likely occurs during fructose-induced salt sensitive hypertension, and it enhances urinary Na + excretion in part through actions on the proximal tubule [ 46 ]. Activation of protein kinase C by Ang II blunts the effects of ANP [ 47 , 48 ] and acute fructose treatment enhances the effects of Ang II via protein kinase C when rats are fed a low-salt diet [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…(30) Our laboratory has shown that ANP stimulates dopamine uptake by tubular kidney cells, through the stimulation of NPRA receptors and protein kinase G (PKG) activation. (11,12,22) Moreover, it has been shown that ANP increases the synthesis of renal dopamine by stimulating the activity of dopa decarboxylase. (31) In this insulin-resistance model, and as a result of low levels of plasma ANP, a reduction in both synthesis and uptake of dopamine by tubular cells would be expected as a consequence of reduced…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression was semiquantitatively analyzed using western blot technique, as previously described. (22) Renal expression of Na+/K+-ATPase was determined using anti-Na+/K+-ATPase antibody (Amersham, dilution 1: 8000), renal expression of NPRA, using anti-NPRA antibody (Santa Cruz Biotechnology, dilution 1: 7500), and expression of NPRC, using anti-NPRC antibody (Santa Cruz Biotechnology, dilution 1: 400). Biotinylated IgG anti-rabbit antibody (GE Healthcare Life Sciences, dilution 1: 2000) and streptavidin conjugated with radish peroxidase (GE Healthcare Life Sciences, dilution of 1: 2000) were used for secondary and tertiary reactions, respectively.…”
Section: Protein Expression Analysis By Western Blot Techniquementioning
confidence: 99%
“…However, the clinical efficacy of dopamine infusion has been questioned by a number of clinical studies that indicate that exogenous dopamine lacks effect on promoting renal sodium and water excretion in pathological conditions [2833]. In this way, we have recently reported that an alteration in dopamine tubular transport by OCTs may decrease dopamine bioavailability into the lumen and impair the interaction of dopamine with D1 and D2 receptors [34]. Therefore, a full activity of OCTs is not only necessary to elicit dopamine diuretic and natriuretic actions when it is exogenously administered to rats but also necessary for ANP to exert its full diuretic and natriuretic effects [34].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we have recently reported that an alteration in dopamine tubular transport by OCTs may decrease dopamine bioavailability into the lumen and impair the interaction of dopamine with D1 and D2 receptors [ 34 ]. Therefore, a full activity of OCTs is not only necessary to elicit dopamine diuretic and natriuretic actions when it is exogenously administered to rats but also necessary for ANP to exert its full diuretic and natriuretic effects [ 34 ]. Based on this evidence, understanding how Ang 1-7 and CNP can regulate dopamine transport by OCTs and dopamine availability in renal tubules provides new knowledge about the mechanisms that could impair the diuretic and natriuretic effects of dopamine when it is therapeutically administered in patients with renal failure.…”
Section: Discussionmentioning
confidence: 99%